2003
DOI: 10.4269/ajtmh.2003.69.607
|View full text |Cite
|
Sign up to set email alerts
|

High Seasonal Variation in Entomologic Inoculation Rates in Eritrea, a Semi-Arid Region of Unstable Malaria in Africa

Abstract: Abstract. Entomologic studies were conducted in eight villages to investigate the patterns of malaria transmission in different ecologic zones in Eritrea. Mosquito collections were conducted for 24 months between September 1999 and January 2002. The biting rates of Anopheles arabiensis were highly seasonal, with activity concentrated in the wet season between June and October in the highlands and western lowlands, and between December and March in the coastal region. The biting rates in the western lowlands we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 18 publications
1
30
0
Order By: Relevance
“…arabiensis between two villages located in the same ecological zone in Eritrea. 37 Additionally, Mendis and others 5 reported a negative correlation between the EIR and the distance from breeding sites. Figure 1 illustrates the progression of the transmission season from the start of the rains in October 2005, to peak indoor-resting density of An.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…arabiensis between two villages located in the same ecological zone in Eritrea. 37 Additionally, Mendis and others 5 reported a negative correlation between the EIR and the distance from breeding sites. Figure 1 illustrates the progression of the transmission season from the start of the rains in October 2005, to peak indoor-resting density of An.…”
Section: Discussionmentioning
confidence: 96%
“…arabiensis in different ecologic zones in Eritrea. 37 Finally, in Senegal, EIRs over four consecutive years ranged from 7 to 63 infective bites per person per year, with An. arabiensis responsible for 66% of transmission, An.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…There is a paucity of data on the impact of other agro-ecosystems on malaria transmission in Africa with only a few studies on malaria among communities in sugarcane plantations and those producing cotton and vegetables (Packard, 1986;Ijumba, 1997;Shililu et al, 2003;Dongus et al, 2009). Studies in Kenya have reported a high sporozoite rate for Anopheles gambiae suggesting a high malaria transmission level in the area and low but perennial malaria transmission intensity in sugarcane growing zone (Githeko et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneity in malarial risk has implications for developing and targeting interventions because a single vector control measure such as indoor residual spraying (IRS) may successfully interrupt transmission in a low transmission setting, whereas multiple vector control measures such as IRS, long-lasting insecticide-treated nets (LLINs), larviciding, and/or larval habitat source reduction may be needed to have an impact in high transmission settings. [10][11][12][13][14][15][16][17][18][19][20][21] Therefore, it is necessary to identify and characterize malarial vectors at a local scale to inform successful control strategies.…”
Section: Introductionmentioning
confidence: 99%